Conspicuous consumption of the elite: Social and self-congruity in tourism choices - Correia, Antónia (2017)
This paper relies on social and economic psychology to explore how the travel choices of Portuguese citizens, with different status levels in their daily lives, perceive and adopt different conspicuous travel patterns because of public exposure. To account for the moderated role of public exposure on conspicuous travel patterns, 36 Portuguese citizens were interviewed. Q-methods were applied to explore the varying senses of conspicuous travel choices among citizens with different levels of public exposure, both individually and relative to each other. Complementary qualitative methods were applied, in order to explore how the interviewees construct tourism conspicuous meanings that match their social or self-representations. The results suggest that social contexts moderate the ways in which individuals perceive and experience conspicuous travel. Further, the results show that public groups with higher exposure tend to prefer subtle signals of conspicuousness, in order to differentiate themselves from the mainstream.